GP76 Experience in treatment of bladder exstrophy in newborn girl with apert syndrome. (June 2019) - Gurskaya, Alexandra; Mokrushina, Olga; Nakovkin, Oleg; Sulavko, Maria; Akhmedova, Dinara; Tarzyan, Aram; Zhurkova, Natalya; Savostyanov, Kirill; Pushkov, Alexander; Sladkov, Dmitry
Abstract : Background and aims: Prevalence of bladder exstrophy (BE) is 1 per 30–50 thousand newborns and it is observed in boys 2–6 times more often than in girls. This pathology demands reconstructive surgery at early age. We are presenting the unique clinical case of bladder exstrophy at the girl with the Apert syndrome (its prevalence is 1 per 100–160 thousand newborns) confirmed with molecular genetic testing. Research is focused on identification of appropriate surgical intervention taking into account anomaly form and anatomic features and child general medical condition. Methods: Case history: the child from intact pregnancy and delivery. Multiple congenital anomalies (MCAs) haven't been revealed prenatally. Girl was born on 27.05.2018. At birth the diagnosis of BE and multiple dysembryogenic stigmas was made. The girl was transferred to the NMRCCH in an urgent order at first 24 hours of life. On presentation: BE, total epispadia, divergent labia minora and majora, pubic bones diastasis (up to 4.6 cm). There was a defect on anterior abdominal wall wherethrough bladder mucous membrane was prolapsing. Anus was normal. External sex organs were abnormal, child gender couldn't be identified adequately. The uterus was prolapsing due to anxiety at first 24 hours of life. Acrocephaly, frontal bone persistence, fingers and toes complete syndactyly, uranostaphyloschisis and choanal atresia came under notice. Results: We have performed primary repair of bladder with local flaps on 5 th day. Later we performed rehabilitation measures. Due to molecular genetic testing we revealed heterozygous mutation c.755C> G ( p.Ser252Trp ) in FGFR2 gene (Apert syndrome, autosomal dominant disorder). Long-term outcomes were estimated at six months age. The child is tube fed, puts on weight and develops. Urinary system infections took place twice due to vesicoureteral reflux. Note that bladder voiding and storage functions are adequate. Bladder volume is 60 ml and the interval between urinations is about 1 hour. Following step is to perform neurosurgical treatment. Orthopedic surgery should be performed in older age. Conclusion: Bladder exstrophy treatment in newborns even comorbid with other MCAs is optimal and shall be carried out in referral centres. The choice and validation of surgery method for BE treatment demand personalized approach. Multidisciplinary approach in management of these patients is important in the presence of other MCAs.